2022
DOI: 10.3389/fimmu.2022.811430
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Glucocorticoid and Androgen Receptor Modulator Reduces Viral Entry and Innate Immune Inflammatory Responses in the Syrian Hamster Model of SARS-CoV-2 Infection

Abstract: Despite significant research efforts, treatment options for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remain limited. This is due in part to a lack of therapeutics that increase host defense to the virus. Replication of SARS-CoV-2 in lung tissue is associated with marked infiltration of macrophages and activation of innate immune inflammatory responses that amplify tissue injury. Antagonists of the androgen (AR) and glucocorticoid (GR) receptors have shown efficacy in models of COVID-19 and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 83 publications
2
10
0
Order By: Relevance
“…Additionally, several computational studies have been performed to prove its potential use for treating COVID-19 by interacting with Mpro as well as other key proteins of SARS-CoV-2. , Dutasteride is a 5-α reductase inhibitor and is also a commonly used antiandrogen. Androgen and androgen receptor (AR) modulator are responsible for transcriptionally regulating the cell surface proteins required for viral entry, so blocking the activity of androgen and AR can decrease COVID-19 severity. , A recent clinical trial has indicated that the use of dutasteride can effectively improve clinical symptoms and prevent inflammatory response in COVID-19 patients . In addition, dutasteride has been identified as a promising inhibitor of SARS-CoV-2 Mpro and RNA-dependent RNA polymerase in molecular dynamics simulations performed by Gul et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, several computational studies have been performed to prove its potential use for treating COVID-19 by interacting with Mpro as well as other key proteins of SARS-CoV-2. , Dutasteride is a 5-α reductase inhibitor and is also a commonly used antiandrogen. Androgen and androgen receptor (AR) modulator are responsible for transcriptionally regulating the cell surface proteins required for viral entry, so blocking the activity of androgen and AR can decrease COVID-19 severity. , A recent clinical trial has indicated that the use of dutasteride can effectively improve clinical symptoms and prevent inflammatory response in COVID-19 patients . In addition, dutasteride has been identified as a promising inhibitor of SARS-CoV-2 Mpro and RNA-dependent RNA polymerase in molecular dynamics simulations performed by Gul et al…”
Section: Resultsmentioning
confidence: 99%
“…Androgen and androgen receptor (AR) modulator are responsible for transcriptionally regulating the cell surface proteins required for viral entry, so blocking the activity of androgen and AR can decrease COVID-19 severity. 80,81 A recent clinical trial has indicated that the use of dutasteride can effectively improve clinical symptoms and prevent inflammatory response in COVID-19 patients. 82 In addition, dutasteride has been identified as a promising inhibitor of SARS-CoV-2 Mpro and RNA-dependent RNA polymerase in molecular dynamics simulations performed by Gul et al 83 Apart from the above three drugs, GTP-14564, CHIR-124, AT7867, MK-0773, benperidol, telcagepant, rimegepant, and etrasimod are also probable potential candidates for the treatment against COVID-19.…”
Section: Model Interpretation Based On Attention Mechanismmentioning
confidence: 99%
“…Total cellular quantification conducted in the bronchial epithelium and parenchyma revealed significant decreases in the amount of total cellular populations at 4 DPI and 10 DPI that recovered to baseline at 21 DPI in animals that were transfected with hACE2 adenovirus and subsequently challenged with SARS-CoV-2 (Figure 5). Notably, SARS-CoV-2 infection in other animal models and reports of clinical cases showed compelling histopathological evidence that SARS-CoV-2 infection leads to immune cell infiltration of the lung parenchyma and collapse of bronchial airways, evident through loss of bronchial epithelium (52)(53)(54)(55). The recruitment of immune cells to the lung in SARS-CoV-2 infection can occur as early as 2 DPI and is often progressive and results in permeant lung damage, severe disease, fibrosis, and/or death (54).…”
Section: Discussionmentioning
confidence: 99%
“…Several identified processes offer druggable options for therapeutic treatment. Androgen receptor signaling and its genetic variability have been already linked to COVID-19 severity 11 , 33 and its inhibition proposed as a therapeutic strategy (e.g 34 .). We found several GPCR signaling instances significantly enriched in our network, in particular those related to G i and G q signaling, which mediate vascular inflammation.…”
Section: Discussionmentioning
confidence: 99%